Developing instruments of teacher’s perception of critical thinking in elementary school - Eni Rahmawati; Harun Harun (Intelektual Pustaka Media Utama, 2019)
This study aims to develop the teacher's perceptions of critical thinking in science learning in elementary schools. The samples in this study were 50 elementary school teachers in Central Java. Selection of samples employed convenience sampling. The instruments in this study used a modified Likert Scale. The validity tests used in this research were content validity and construct validity. Content validity was measured using CVR (Content Validity Ratio) and construct validity was measured using EFA (Exploratory Factor Analysis). By using SPSS, reliability estimation was obtained with the Cronbach Alpha formula 0.83 and it can be stated that the instruments for evaluating teacher perceptions of critical thinking in science learning are reliable.